Fabrication and supercapacitive properties of hierarchical porous carbon from polyacrylonitrile. (December 2015) - Chen, Guangpin; Zhai, Wenli; Wang, Zhanghui; Yu, Jianguo; Wang, Fengqin; Zhao, Yongnan; Li, Guodong
Graphical abstract: Highlights: Hierarchical porous carbon is facilely fabricated by phase inversion and carbonization. The hierarchical porous carbon are abundant in micro- and macropores. The hierarchical porous carbon exhibit excellent supercapacitive performances. Abstract: A facile and scale-up route was developed to fabricate hierarchical porous carbon (HPC) materials from polyacrylonitrile through phase inversion and carbonization. The phase inversion produced macroporous polymer by the diffusion of the organic solvent. Controlled heat treatment produced hierarchical porous carbon that were abundant in interconnected micro- and macropores with the micropore size of 0.53–0.60 nm. XPS spectra of C1S indicated the abundance of surface O-containing groups. CV curves of HPC9 at various scan rates implied a superior rate capability. The EIS curve showed a typical supercapacitive behavior with nearly vertical line in low frequency. Supercapacitor assessments in 6 M KOH solution revealed that HPC9 possessed high capacitances of 156 F g −1 and 34.6 μF cm −2 at 0.2 A g −1 . No obvious fading occurred in the capacitance and coulombic efficiency over 8000 cycles. Oxidation modified sample HPCO9 gave enhanced capacitances of 173.2 F g −1 and 60.1 μF cm −2 .